Investigation on the influence of intensity scintillation and beam wander in space optical uplink DWDM communication system. Issue 2 (2nd April 2016) - Li, Mi; Chen, Mengji; Zhang, Xuping; Cong, Hengji; Song, Yuejiang; Lu, Yuangang
Abstract: Dense wavelength division multiplexing (DWDM) has been widely applied in ground optical communication. However, the technology of DWDM is still not mature enough in the space optical communication system. In order to further advance the use of DWDM into space optical communication, the probability density function (PDF) and the bit-error rate (BER) performance of DWDM is investigated in uplink communications under the influence of atmospheric turbulence, consisting of intensity scintillation and beam wander caused by atmospheric turbulence. Numerical results show that the atmospheric turbulence has a great impact on BER and PDF, and wavelength, divergence angel, and other relevant parameters should be carefully considered in this DWDM system. This work can be conducive for improving DWDM design of space optical uplink communication systems.